Food Security and Leukocyte Telomere Length in Adult Americans. (29th August 2017) - Mazidi, Mohsen; Kengne, Andre Pascal; Vatanparast, Hassan
Abstract : Background and Purpose . Leukocyte telomere length (LTL) is a biomarker of biologic age. Whether food security status modulates LTL is still unknown. We investigated the association between food security and LTL in participants of the 1999–2002 US National Health and Nutrition Examination Survey (NHANES). Methods . Analysis of covariance (ANCOVA) was used to evaluate the association between food security categories and LTL controlling for sex, race, and education and accounting for the survey design and sample weights. Results . We included 10, 888 participants with 5228 (48.0%) being men. They were aged on average 44.1 years. In all, 2362 (21.7%) had less than high school, 2787 (25.6%) had achieved high school, while 5705 (52.5%) had done more than high school. In sex-, race-, and education-adjusted ANCOVA, average LTL (T/S ratio) for participants with high food security versus those with marginal, low, or very low food security was 1.32 versus 1.20 for the age group 25–35 years and 1.26 versus 1.11 for the 35–45 years, (p < 0.001 ). Conclusion . The association between food insecurity and LTL shortening in young adults suggest that some of the future effects of food insecurity on chronic disease risk in this population could be mediated by telomere shortening.